The effect of insulin to decrease neointimal growth after arterial injury is endothelial nitric oxide synthase-dependent. Issue 1 (July 2015) - Guo, June; Breen, Danna M.; Pereira, Troy J.; Dalvi, Prasad S.; Zhang, Hangjun; Mori, Yusaku; Ghanim, Husam; Tumiati, Laura; Fantus, I. George; Bendeck, Michelle P.; Dandona, Paresh; Rao, Vivek; et al.
Abstract In vitro, insulin has mitogenic effects on vascular smooth muscle cells (VSMC) but also has protective effects on endothelial cells by stimulating nitric oxide (NO) production and endothelial nitric oxide synthase (eNOS) expression. Furthermore, NOS inhibition attenuates the effect of insulin to inhibit VSMC migration in vitro. Using an in vivo model, we have previously shown that insulin decreases neointimal growth and cell migration and increases re-endothelialization after arterial injury in normal rats. Since insulin can stimulate NOS, and NO can decrease neointimal growth, we hypothesized that NOS, and more specifically eNOS was required for the effects of insulin in vivo. Rats were given subcutaneous insulin implants (3 U/day) alone or with the NOS inhibitor l-NAME (2 mg kg−1 day−1) 3 days before arterial (carotid or aortic) balloon catheter injury. Insulin decreased both neointimal area (P < 0.01) and cell migration (P < 0.01), and increased re-endothelialization (P < 0.05). All of these effects were prevented by the co-administration of l-NAME. Insulin was found to decrease inducible NOS expression (P < 0.05) but increase eNOS phosphorylation (P < 0.05). These changes were also translated at the functional level where insulin improved endothelial-dependent vasorelaxation. To further study the NOS isoform involved in insulin action, s.c. insulin (0.1 U/day) was given to wild-type and eNOS knockout mice. We found that insulin was effective at decreasing neointimal formation in wild-type mice after wire injury of the femoral artery, whereas this effect of insulin was absent in eNOS knockout mice. These results show that the vasculoprotective effect of insulin after arterial injury is mediated by an eNOS-dependent mechanism.